Cosmopolitan Utilitarianism and the Problem of Local Inaction in a Globalized World (Glocalism: Journal of Culture, Politics and Innovation, 2015)
This article explores the problem of the public acceptability of political inaction as an extreme consequence of cosmopolitan utilitarianism. The case of political inaction as the utility-maximizing public policy option emerges more clearly in the globalized world, because of a misalignment between the electoral body and the persons that the government ought to consider while evaluating the consequences of a given policy. In this context, a situation can easily occur in which the only way to maximize utility in a global context is by renouncing action at the national or local level. However, the problem of inaction should not be interpreted simply as a by-product of globalization. Its origins can be traced to the basic structure of utilitarianism as a normative consequentialist theory. This drawback can even present itself at the local level in a less visible form. One example is that in which the performance of a supererogatory act in the exercise of public office leads to a reduction in overall utility. The aim of the article is to demonstrate that cosmopolitan utilitarianism can bind the decision maker to a series of inactions at the global and local levels that contradict his own mandate, generating a dangerous moral confusion in the implementation of public policies. This can seriously threaten the universal applicability of cosmopolitan utilitarianism as a normative political theory, especially in the age of globalization.
Keywords: cosmopolitanism; utilitarianism; inaction; local